MELUKIS SEBAGAI MEDIA PENGEMBANGAN PENDIDIKAN KREATIVITAS PADA ANAK-ANAK - Ana Rosmiati (Institut Seni Indonesia Surakarta, 2012)
Painting is an activity full of stimulation of the growth and development of children. As well as writing and playing activities, painting has benefits for child development. Painting has benefits that help activate the right brain ‘creativity can thrive. The problem in that will be described in this paper is the development of alternative methods of painting as a medium of education. This paper aims to discover the impact of media use to paint on children’s learning. The benefits of this research are: (a) help the child is able to create something based on imagination; (b) can be adopted by teachers and parents as a means of education, particularly early childhood, (c) can be used as a source of material and inspiration for performers (d) to motivate young children to get to know and appreciate the works of art, especially the art of painting; (e) assist early childhood to develop sensitivity, and (f) to motivate young children to express themselves using a variety of media through painting. Sources of data in this study were collected through (1) the study of literature contained in many libraries as in Play Group and workers, library Surakarta, (2) direct observation to see learning methods, and (3) are supported by in-depth interviews conducted sound recording the informant. Painting for children will learn to invent or create, pouring his ideas, as well as visualize and realize the imagination in a work; help the development of the cognitive, emotional intelligence and intelligence their motor; Hone talents of children who may have a significant impact on the ability and the skills they in the future, and to foster interest in learning, as well as methods of learning and creativity-based education, providing children allowed to express their thoughts and feelings through images without always given mock object. Key words : painting, children, creativity Pengantar